2017
DOI: 10.1177/0194599817702622
|View full text |Cite
|
Sign up to set email alerts
|

Case‐Logging Practices in Otolaryngology Residency Training: National Survey of Residents and Program Directors

Abstract: Objective (1) Evaluate the consistency and manner in which otolaryngology residents log surgical cases. (2) Assess the extent of instruction and guidance provided by program directors on case-logging practices. Study Design Cross-sectional national survey. Setting Accreditation Council for Graduate Medical Education otolaryngology residency programs in the United States. Subjects and Methods US otolaryngology residents, postgraduate year 2 through graduating chiefs as of July 2016, were recruited to respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Since ascertaining competence is so difficult, we often will use surrogate markers, such as case logs, procedural checklists, and summative evaluations . Case logs can be inaccurate, and deciding whether an individual was the assistant surgeon, resident surgeon, or supervising surgeon is open to interpretation . For example, to meet the key indicator for ossiculoplasty and stapedectomy, a resident must complete 10 cases as primary surgeon, where they perform greater than 50% of the case in addition to the key portions of the procedure .…”
Section: Discussionmentioning
confidence: 99%
“…Since ascertaining competence is so difficult, we often will use surrogate markers, such as case logs, procedural checklists, and summative evaluations . Case logs can be inaccurate, and deciding whether an individual was the assistant surgeon, resident surgeon, or supervising surgeon is open to interpretation . For example, to meet the key indicator for ossiculoplasty and stapedectomy, a resident must complete 10 cases as primary surgeon, where they perform greater than 50% of the case in addition to the key portions of the procedure .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, case logs are notoriously inaccurate largely due to underreporting of cases performed despite program directors advising residents to log all procedures. [ 5 ] This is particularly true for procedures performed outside of the operating room and common procedures, both of which dominated our results. [ 5 ] Case logging methods also vary greatly between programs.…”
Section: Discussionmentioning
confidence: 93%
“…[ 5 ] This is particularly true for procedures performed outside of the operating room and common procedures, both of which dominated our results. [ 5 ] Case logging methods also vary greatly between programs. Moving forward with a national CBD curriculum, case logging will be standardized and submitted prior to graduation from residency to the Royal College of Physicians and Surgeons of Canada (RCPSC).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cadish et al investigated multiple specialty residents in a single training institution and found that nearly two-thirds of resident physicians considered the "case logs" work to be highly arduous, which affected the willingness, frequency, and accuracy of registration [21]. Dermody et al conducted an anonymous questionnaire survey of all otolaryngology-head and neck surgery residents and program directors (PDs) in the US; the survey revealed that most of the residents and PDs believed that accuracy was not high for online surgical case logs prescribed by the ACGME [22]. Therefore, whether these surgical case logs genuinely re ect the operative ability of residents is questionable [23].…”
Section: Discussionmentioning
confidence: 99%